The educator's perspective: knowledge, attitude and practices on occupational safety and health at school among primary and secondary school teachers - Mohamad Yusoff, Nursyuhada; How, Vivien; Azmi, Sabrina; Othman, Khairuddin (Malaysian Public Health Physicians' Association, 2019)
Introduction: School can be considered as a relatively moderate risk working environment due to the various hazards assembled in the school. Nevertheless, Occupational Safety and Health (OSH) training is yet to formally inclusive into teachers’ training module, and the current one-off or ad-hoc OSH training mainly targeted among school students. The different OSH awareness exists among teacher and student have hinder the provision of sustainable and effective safety and health training program at school levels. Objective: To assess the knowledge, attitude and practice among primary and secondary school teachers towards OSH at the school environment. Method: A cross-sectional survey carried out at three (3) primary schools and three (3) secondary schools after stratified random sampling. School teachers from these schools were randomly selected among those who had at least one year work experience as permanent teacher at the current school through the fishbowl technique. A structured questionnaire was used and total 136 teachers were assessed on their knowledge, attitude and practices on OSH at schools. Result: Study found that primary and secondary school teachers have different knowledge, attitude and practices of OSH at school levels. Overall, the knowledge level of secondary school teacher (62.1% of high to medium knowledge levels) are higher than the primary school teachers (41.1% of high to medium knowledge levels); at the same time, 93.1% of secondary school teachers show positive attitude while 88.5% of primary school teachers show positive attitude on safety and health at schools. In general, OSH practice level among the primary (88.5%) and secondary school teachers (86.2%) are at relatively good levels. Besides, there is positive association with knowledge and attitude on OSH behavior among primary school teachers. Apart of this, there is positive but relatively weak association with knowledge and practices and knowledge and attitudes among primary and secondary school teachers. Conclusion: Considering the background differences between primary and secondary school teachers, a sustainable OSH learning mechanism should be planned and designed together with OSH practitioners and Ministry of Education to achieve a sustainable safety and healthy sound school environment for teacher to work and for students to learn.